1997
DOI: 10.1021/ma970655t
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecular Weight and Regioregularity on the Polymorphic Behavior of Poly(3-decylthiophenes)

Abstract: High molecular mass and high regioregularity favor the more common polymorph (form I) of poly(3-alkylthiophenes) and substantially extend toward high temperatures the existence domain of the 2D mesomorphic phase, which these systems access above 70−80 °C. Morphological observations indicate that in thin films of form I the planar polythiophene main chains lie roughly edge-on parallel to the film surface, while side chains are approximately orthogonal to the substrate. Evidence relative to the second polymorph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
187
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(210 citation statements)
references
References 24 publications
20
187
3
Order By: Relevance
“…These periods correspond well with the ones extracted from the angularly averaged ED line scans in Figure 3 as well as the lamellar periods reported in the literature for form I P3ATs (vide infra). 5,35 As seen in Figure 2, the length of the side chains has a clear influence on the proportion of nanocrystals observed by HR-TEM. As the length of the alkyl side chains increases, a higher fraction of face-on oriented nanocrystallites is evidenced.…”
Section: Methodsmentioning
confidence: 92%
“…These periods correspond well with the ones extracted from the angularly averaged ED line scans in Figure 3 as well as the lamellar periods reported in the literature for form I P3ATs (vide infra). 5,35 As seen in Figure 2, the length of the side chains has a clear influence on the proportion of nanocrystals observed by HR-TEM. As the length of the alkyl side chains increases, a higher fraction of face-on oriented nanocrystallites is evidenced.…”
Section: Methodsmentioning
confidence: 92%
“…11,13 Alternatively, Form II of poly(3-butylthiophene) (P3BT) can be obtained by exposure of the cast films to CS 2 vapors. 17,18 Meille et al 14 suggested that the occurrence of Form II is related to the molecular mass and the regioregularity of the samples. For P3HT, Form II was reported only for low molecular mass, that is, 2-3 kDa.…”
Section: Polymorphismmentioning
confidence: 99%
“…As illustrated by the wide-angle X-ray diffraction (WAXD) pattern shown in Figure 1, the reflection peak from the (100) Miller plane of Form I, which is around 2h = 7.2°(d-spacing 12.3 Å) in a WAXD profile, gradually disappears upon exposure to carbon disulfide vapor, accompanied by the appearance of the (100) reflection of Form II at 2h ≈ 9.2°(d-spacing 9.6 Å). [15,16] The tremendous decreased intensity of this reflection may be associated with the changed orientation of the polymer chains. However, this still gives evidence that the crystallographic transition of P3BT from Form I to Form II takes place as the specimen is exposed to CS 2 vapor.…”
mentioning
confidence: 99%
“…[16][17][18][19] However, so far, no Form II has been explicitly obtained from P3AT with short alkyl segments, for instance, P3BT with side substitution of the butyl segment. This was previously attributed to the interaction between the short alkyl segments being too weak.…”
mentioning
confidence: 99%